Gender- and age-specific rates of heart failure and other adverse cardiovascular outcomes in systemic sclerosis. (8th February 2022) - Sun, Guoli; Yafasova, Adelina; Andersson, Charlotte; McMurray, John J V; Jhund, Pardeep S; Docherty, Kieran F; Faurschou, Mikkel; Nielsen, Christoffer T; Schou, Morten; Gislason, Gunnar H; Torp-Pedersen, Christian; Fosbøl, Emil L; et al.
Abstract: Objective: To investigate the long-term rates of heart failure (HF) and other adverse cardiovascular outcomes, including arrhythmias, myocardial infarction, ischaemic stroke, venous thromboembolism, pulmonary hypertension and pericarditis, in SSc patients according to gender and age. Methods: Using Danish nationwide registries, SSc patients (diagnosed from 1996 to 2018) were matched with four controls from the background population by gender, age and comorbidities. Cox regression was used to compare the rates of cardiovascular outcomes between SSc patients and controls and the rate of mortality between SSc patients developing HF and HF patients without SSc, according to gender and age (above/below median). Results: In total, 1569 SSc patients were matched with 6276 non-SSc controls (median age 55 years, 80.4% women, median follow-up 7.3 years). SSc had a higher rate of HF in both women [HR 2.99 (95% CI 2.18, 4.09)] and men [HR 3.01 (1.83, 4.95)] ( P interaction  = 0.88), with similar trends for other cardiovascular outcomes. SSc had a higher rate of HF in patients <55 years of age [HR 4.14 (95% CI 2.54, 6.74)] and ≥55 years [HR 2.74 (1.98, 3.78)] ( P interaction  = 0.22), with similar trends for other cardiovascular outcomes. SSc patients with new-onset HF had a higher rate of mortality than HF patients without a history of SSc, irrespective of gender ( P interaction  = 0.53) and age ( P interaction  = 0.43). Conclusions: SSc was associated with higher rates of HF and other cardiovascular outcomes than matched controls, irrespective of gender and age. Among patients with new-onset HF, a history of SSc was associated with higher mortality.